Potted rose cultivars with paclobutrazol drench applications - Grossi, José Antonio Saraiva; Carvalho-Zanão, Maristela Pereira; Zanão Júnior, Luiz Antônio; Pereira, Natalia (Ciência Rural, 2018)
Growth retardants, such as paclobutrazol, reduce plant height, and thus enable commercialization of larger ornamental plants in pots. The aim of this research was to evaluate the size, yield and flower quality of two rose cultivars as a function of various paclobutrazol applications to growing substrate. Treatments consisted of two cultivars (Yellow Terrazza® and Shiny Terrazza®) planted in plastic pots and five paclobutrazol doses (0, 0.5, 1.0, 1.5, and 2.0mg pot-1). The experiment was carried out in a greenhouse. Experimental design was randomized blocks with four replications. The following traits were evaluated: plant height; stem diameter, number of flowers and leaves of floral stem; length of flower bud; floral cycle, leaf area; flower diameter and floral longevity; chlorophyll content in leaves; and yield. Paclobutrazol improved the quality and esthetics of flowers of both cultivars. It also reduced leaf dry matter production, plant height, flower height and diameter and increased chlorophyll content and flower longevity. Paclobutrazol effectively reduced plant height, producing a harmonious relationship between the plant and the pot, without phytotoxicity. Therefore, we suggested applying 2.0mgpot-1 of paclobutrazol to the substrate of Yellow Terrazza® and Shiny Terrazza® rose cultivars.

A aplicação de retardantes de crescimento, como o paclobutrazol, reduz a altura das plantas e tem possibilitado a comercialização de algumas espécies ornamentais de maior porte em vasos. Objetivou-se com este estudo avaliar porte, produção e qualidade da flor de duas cultivares de roseira cultivadas em vaso em função da aplicação de doses de paclobutrazol no substrato. Os tratamentos foram dispostos em esquema fatorial 2x5, com duas cultivares de roseira (Yellow Terrazza® e Shiny Terrazza®) e cinco doses de paclobutrazol (0; 0,5; 1,0; 1,5 e 2,0 mg vaso-1). O experimento foi conduzido em vasos plásticos sob ambiente protegido, em delineamento de blocos ao acaso com quatro repetições. Foram avaliados a altura das plantas; diâmetro, número de flores e folhas da haste floral; comprimento do botão floral; ciclo, área foliar; diâmetro floral e longevidade floral; teor de clorofila nas folhas e produção. A aplicação de paclobutrazol no substrato proporcionou melhoria na qualidade floral e estética de ambas cultivares de roseira. Também reduziu a produção de matéria seca foliar, altura da planta e diâmetro floral e aumentou o teor de clorofila e a longevidade floral. O paclobutrazol foi eficiente em reduzir a altura, conferindo uma relação harmoniosa entre a planta e o vaso, sem causar sintomas de toxidez e alterações morfológicas. Sugere-se a aplicação no substrato de 2mg vaso-1 de paclobutrazol para as cultivares de roseira Yellow Terrazza® e Shiny Terrazza® produzidas em vasos.
Keywords: Rosa hybrid L.; Growth retardant; Floriculture; Rosa hybrida L.; Retardante de crescimento; Floricultura